Cooperation a political, economic, and social theory - Harcourt, Bernard E. 1963- (Columbia University Press, 2024)
Liberal democracy is in crisis around the world, unable to address pressing problems such as climate change. There is, however, another path—cooperation democracy. From consumer co-ops to credit unions, worker cooperatives to insurance mutuals, nonprofits to mutual aid, countless examples prove that people working together can extend the ideals of participatory democracy and sustainability into every aspect of their lives. These forms of cooperation do not depend on electoral politics. Instead, they harness the longstanding practices and values of cooperatives: self-determination, democratic participation, equity, solidarity, and respect for the environment.Bernard E. Harcourt develops a transformative theory and practice that builds on worldwide models of successful cooperation. He identifies the most promising forms of cooperative initiatives and then distills their lessons into an integrated framework: Coöperism. This is a political theory grounded on recognition of our interdependence. It is an economic theory that can ensure equitable distribution of wealth. Finally, it is a social theory that replaces the punishment paradigm with a cooperation paradigm.A creative work of normative critical theory, Cooperation provides a positive vision for addressing our most urgent challenges today. Harcourt shows that by drawing on the core values of cooperation and the power of people working together, a new world of cooperation democracy is within our grasp
Getting Started; 1. The Urgency of Coöperism; 2. The Ubiquity of Cooperation; 3. The Simplicity of Cooperation; 4. The Political Theory of Coöperism; 5. The Economic Theory of Coöperism; 6. The Social Theory of Coöperism; 7. A Defense of Coöperism; 8. Cooperation Democracy; Acknowledgments; Notes; Bibliography; Index
Keywords: bisacsh / PHILOSOPHY / Movements / Critical Theory; bisacsh / SOCIAL SCIENCE / Activism & Social Justice; bisacsh / POLITICAL SCIENCE / History & Theory; Politische Theorie; Kooperation; Demokratie; Politische Beteiligung